Integrasi Ayat-Ayat Al-Qur’an Pada Pembelajaran Biologi - Sonia Nurul Ayunda; Arsya Gusnita; Fani Fenty Aradia; Ardi (EDU-BIO: Jurnal Pendidikan Biologi, 2023)
Biological learning reveals scientific truths and can be carried out in a number of ways. Scientific enquiry or research, one of the methods that can be applied. a flawless and comprehensive system that takes into account every aspect of human existence, including scientific pursuits or research, has been provided through the Quran and Hadith. The Qur'an has shown a perfect blend as a source of inspiration for science. To make learning about biology more relevant, this research tries to connect and incorporate appropriate Quranic verses for it. This research was conducted using the library research method. The findings of this study show that incorporating Quranic verses into biology lessons has a high probability of success. Several biological sources show the connection between the topic of Qur'anic integration and biological education. The essential discussions in the Qur'an and biology subject matter are the same, but the language and explanations are presented differently.